A Comparative Analysis of Translation Techniques between YouTube Subtitle Translation and the DeepL Translation Tool in the Song Lyrics of Shake It Off by Taylor Swift - Agneso Feronika Limbong; Haidah Situmorang; Juliva Viona Banjarnahor; Aryadi Manuel Gultom (Merwinspy Publisher, 2025)
This study uses a descriptive qualitative approach to examine the translation techniques used in the translated version of the song